Analisis Penceraian Pada Kesehatan Mental Anak Di Desa Wringin Bondowoso - Hidayat, Nur Taufiq; Hakim, Lukmanul; Rifa, Muhammad Bahtiar; Fitriana, Ani Qotus Zuhro’ (CV. ITTC INDONESIA, 2022)
This study aims to describe the effect of divorce on children's mental health. Where this research was conducted on children in Wringin Bondowoso Village through a qualitative approach with a case study type of research. Methods of data collection carried out by means of observation and interviews. From the results of the study, the following data were obtained: (1) divorce is the breaking of the marriage bond due to the decision of both parties, which religiously and legally no longer binds as a husband and wife (2) divorce is caused by several causes, such as financial problems and not fulfilling economic needs (3) parental divorce greatly impacts children, especially on children's mental health.